Analisis Modal Kerja Usaha Kecil Dalam Rangka Peningkatan Kinerja Usaha Menghadapi Era Pasar Bebas: Kabupaten Lumajang - M. Wimbo Wiyono; Oyong Lisa (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2011)
Obstacles faced in developing small businesses in the City of small businesses in particular Lumajang Lumajang similar to problems faced by small businesses nationally, the gap between medium and large businesses increasingly widened. Small businesses in Lumajang generally weak in the capital, difficulties in obtaining capital, including working capital, weaknesses in management and low quality of human resources. The results of calculations and studies have been conducted that shows a general hypothesis expressed in this research can be proved, for the following reasons: (a) The results of calculation of working capital requirements based on the amount of sales volume achievement generally showed nearly (90%) small businesses that use the lack of working capital. (b) The effect of poor working capital management also affect the competitive ability of small businesses so that if this continued without looking for solutions not covered will likely affect the existence and competitiveness of small businesses in the future, especially in the era or the era of Global AFTA